A new alien gastropod Pseudorhaphitoma iodolabiata (Hornung & Mermod, 1928) (Mangeliidae, Mollusca) in the Mediterranean Sea - OZTURK, B. (Mediterranean Marine Science, 2012)
The study documents the occurrence of a new alien gastropod Pseudorhaphitoma iodolabiata in the Mediterranean Sea, collected in Iskenderun Bay, Turkey, on September 2011. This record increases to 213 the number of alien molluscs in the Mediterranean.